The Influence of Managerial Leadership on the Effectiveness of Work Teams in the National Manufacturing Industry - Herbert Hot Ojahan Siagian; Jeffry H. Sinaulan (Universitas Pendidikan Ganesha, 2026)
The low effectiveness of working hours in the national manufacturing industry is due to leadership styles that are not yet adaptive to the dynamics of industrial change. The urgency of this research arises because the manufacturing sector is the backbone of the Indonesian economy, contributing 18.98% of national GDP in 2024, but still faces challenges in employee productivity and retention. The purpose of this study is to analyse the influence of transformational, transactional, and situational leadership styles on the effectiveness of working hours. The study sample consisted of 300 managers and production team members in the textile, automotive, and electronics sectors. Data were collected through a five-point Likert scale questionnaire and analysed using Structural Equation Modeling (SEM). The results show that transformational leadership has a significant effect on productivity (β = 0.42; p = 0.001), motivation (β = 0.39; p = 0.002), and collaboration (β = 0.35; p = 0.004), but has a negative impact on retention (β = -0.21; p = 0.015). Transactional and situational leadership also had a positive effect on productivity (β=0.28 and β=0.33). The findings indicate that the combination of adaptive leadership styles increases overall team effectiveness (Adjusted R²=0.82). The study's conclusions emphasize the importance of a balance between inspiration, reward systems, and adaptive equity. The study's implications recommend transformational leadership training and participatory reward systems to improve employee performance and retention in the Indonesian manufacturing sector.